Kardiochirurgia DorosłychEarly results of unipolar endocardial radiofrequency ablation for permanent atrial fibrillation in patients with mitral valve disease - Widenka, Kazimierz; Kurowicki, Arkadiusz; Kolowca, Maciej; Bąk, Janusz; Stącel, Tomasz; Szymanik, Izabela; Mazur, Witold; Żurek, Sławomir; Domagała, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Mitral valve insufficiency is often correlated with dysrhythmia such as atrial fibrillation (AF). The method of concomitant correction of mitral valve disease and unipolar endocardial surgical radiofrequency ablation is a very promising option. Material and methods: Ten patients suffering from significant mitral valve insufficiency and permanent atrial fibrillation who were subject to prospective analysis entered the study. Between November 2006 and April 2007 they underwent concomitant procedure of either mitral valve repair or replacement with unipolar endocardial surgical radiofrequency ablation. Results: In the postoperative period stable sinus rhythm was observed in 70% of patients (n=7). One patient with preoperative renal failure died of multiorgan failure in the early postoperative period. Conclusions: Unipolar endocardial left atrial surgical radiofrequency ablation combined with mitral valve surgery during a single procedure is very safe, repeatable and highly effective in achieving and maintaining sinus rhythm.